2021
DOI: 10.1111/pce.14008
|View full text |Cite
|
Sign up to set email alerts
|

Protein modification: A critical modulator in the interaction between geminiviruses and host plants

Abstract: Geminiviruses are a large group of single-stranded DNA viruses that infect plants and cause severe agricultural losses worldwide. Given geminiviruses only have small genomes that encode a few proteins, viral factors have to interact with host components to establish an environment suitable for virus infection, whilst the host immunity system recognizes and targets these viral components during infection.Post-translational protein modifications, such as phosphorylation, lipidation, ubiquitination, SUMOylation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The switch from one function to another requires tight regulation, and this can be achieved through post-translational modifications, as has been shown for animal viruses in a number of cases [1][2][3]. For plant viruses, the number of examples is much narrower, and include protein modifications such as phosphorylation, glycosylation, lipidation or ubiquitination [4][5][6][7]. Cysteine oxidations, which are redox-dependent post-translational modifications, have been shown to play regulatory roles for animal virus and host proteins during infections [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The switch from one function to another requires tight regulation, and this can be achieved through post-translational modifications, as has been shown for animal viruses in a number of cases [1][2][3]. For plant viruses, the number of examples is much narrower, and include protein modifications such as phosphorylation, glycosylation, lipidation or ubiquitination [4][5][6][7]. Cysteine oxidations, which are redox-dependent post-translational modifications, have been shown to play regulatory roles for animal virus and host proteins during infections [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that phosphorylated proteins are involved in the regulation of numerous cellular signals with host cells, influencing nearly one-third of protein functions [7]. It is evident that protein phosphorylation is critical for controlling the interaction between pathogens and host cells [8]. T. gondii, for instance, has evolved to reprogram host biological processes by modifying the phosphorylation status of host proteins [9].…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, the virus must move intracellularly, intercellularly, and systemically, invading new cells and making virions available for acquisition by the vector. In order to accomplish a successful infection, geminiviruses must tailor the cellular environment to favour their replication and spread; for this purpose, they modify the transcriptional landscape of the infected cell, re-direct posttranscriptional modifications, and interfere with hormone signalling, among other things (reviewed in Aguilar et al, 2020;Kumar, 2019;Liu et al, 2021), ultimately suppressing anti-viral defences, creating conditions favourable to viral replication, and manipulating plant development. Although geminivirus-encoded proteins are described as multifunctional, how the plethora of tasks required for a fruitful infection can be performed by only 4-8 proteins is an intriguing biological puzzle.…”
Section: Introductionmentioning
confidence: 99%